Epigenetic Mechanisms of Rubinstein-Taybi Syndrome - Park, Elizabeth; Kim, Yunha; Ryu, Hyun; Kowall, Neil W.; Lee, Junghee; Ryu, Hoon (Humana Press, Inc., 2014)
Rubinstein-Taybi syndrome (RTS) is an incurable genetic disorder with combination of mental retardation and physical features including broad thumbs and toes, craniofacial abnormalities, and growth deficiency. While the autosomal dominant mode of transmission is limitedly known, the majority of cases are attributable to de novo mutations in RTS. The first identified gene associated with RTS is CREB-binding protein (CREBBP/CBP). Alterations of the epigenetic 'histone code' due to dysfunction of the CBP histone acetyltransferase activity deregulate gene transcriptions that are prominently linked to RTS pathogenesis. In this review, we discuss how CBP mutation contributes to modifications of histone and how histone deacetylase inhibitors are therapeutically applicable to epigenetic conditioning in RTS. Since most genetic mutations are irreversible and therapeutic approaches are limited, therapeutic targeting of reversible epigenetic components altered in RTS may be an ideal strategy. Expeditious further study on the role of the epigenetic mechanisms in RTS is encouraged to identify novel epigenetic markers and therapeutic targets to treat RTS.